Digital Information System Transformation Population Data Management Solution for Galanggang Village, West Bandung Regency - Heri Wahyudi; Rohmat Nur Ibrahim; Feri Alpiyasin; Komarudin Komarudin; Miranti Andhita Scantya (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
The community service team of lecturers and students from STMIK Mardira Indonesia has implemented a project to manage demographic data services in Galanggang Village, Batujajar, West Bandung. This project involved the team's efforts to advance information technology via a website that includes essential components such as the homepage, admin and community login pages, village population statistics, records of deceased individuals, data on individuals relocating, and a compilation of relocation requests. The project aims to improve efficiency and openness in managing demographic data for village administrators and the local community. The methodology encompassed the advancement of information technology and the training of village leaders and the community to optimize the application's use. The project successfully implemented the Galanggang Village website application (SIDELA) for managing demographic data. This application enables village administrators and citizens to handle demographic data, including relocation and mortality information, efficiently. This community service initiative has profoundly influenced village administrators and inhabitants of Galanggang by enhancing the implementation of information technology for improved demographic data management. These measures are anticipated to be perpetually enhanced to yield sustainable advantages for village administrators and citizens of Galanggang, West Bandung Regency.